Combination treatment of clinacanthus nutans extract with cisplatin against breast cancer cell line, MCF-7 / Akmal Arif Daud, Nurul Anieza Osman and Normala Abd Latip - Daud, Akmal Arif; Osman, Nurul Anieza; Abd Latip, Normala (Faculty of Pharmacy, 2024)
Chemotherapy is one of the treatments for cancer and among the important agent is cisplatin. However, owing to the adverse effects associated with modern medicine, patients often explore traditional herbal remedies for cancer management. Clinacanthus nutans is widely believed to possess healing properties for various ailments, including cancer. The cultural and traditional background of this plant increases its acceptance among patients seeking alternative or complementary treatments. There exists a growing concern regarding the potential impact of C. nutans on the efficacy of cisplatin in treating breast cancer. Thus, this study aims to assess the anticancer properties of C. nutans water extract on MCF-7 cells and examine the interaction between C. nutans water extract and cisplatin on MCF-7 cells. Cells were treated separately with C. nutans water extract or cisplatin to determine their respective IC 50 values. Subsequently, a combination treatment involving C. nutans water extract and cisplatin was administered, and the percentage of MCF-7 cell viability was assessed using MTT assay. The findings indicate that C. nutans water extract exhibits limited anticancer activity on MCF-7 cells and demonstrates an antagonistic interaction with cisplatin on MCF7 cells. Further research is warranted to explore potential interactions between C. nutans and other anticancer agents, thereby paving the way for more informed approaches in cancer treatment.